Pemanfaatan Video Edukasi Dalam Rangka Penguatan Kesadaran Hukum Penggunaan Obat Keras Di SMA N 7 Kota Semarang - Erawati, Ambar Dwi; Retnaningrum, Okti Trihastuti Dyah (Jurnal Pengabdian Masyarakat (ABDIRA), 2024)
Gevaarlijk drugs are drugs that should not be traded freely because hard drugs harm the body if used irrationally. The abuse of hard drugs is often abused by the community, especially students. The method used is to provide assistance with 1 time of counseling, mentoring and 1 evaluation, then the video is shared with students of SMA N 7 Semarang class X to be used and can be spread to other friends. The target of this activity is that SMA 7 students understand hard drugs and be careful in their use. The service implementation team made an educational video that can be used by teenagers to avoid the use of hard drugs. The video was disseminated to students of SMA N 7 Semarang City with the result that there was an increase in knowledge about the dangers of irrational use of hard drugs, and sanctions when vibrating hard drugs. Increasing knowledge about the dangers of irrational use of hard drugs and sanctions for abusers is very important for the community, especially adolescents, to improve the morale of the nation.